Impact of export and gross domestic product towards foreign direct investment inflows in Malaysia - Abu Hassan Asari, Fadli Fizari; Shamsudin, Norazidah; Hamid Abd Kadir, Rhaudhah Anis; Baharuddin, Nurul Syuhada; Affandi, Salwani; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Malaysia has been encouraging Foreign Direct Investment (FDI) inflows not only for its role in technology transfer but also for its economic contribution. Identifying the factors affecting the FDI is important in explaining the Malaysian economy performance. Therefore, the aim of this study is to investigate the impact Of Export (EXP) and economic growth on FDI inflows performance in Malaysia for a period of 30 years from 1979 to 2008 using the Vector Error Correction Model (VECM). In this paper, the economic growth shall be denoted by the Gross Domestic Product (GDP). 'Granger no causality test' or mostly know as Causality Test was used to test the direction of causality between the variables whereas Johansen Cointegration Test was employed to gauge the long run relationship. According to the findings, GDP 'granger cause' FDI runs unidirectionally on a short term basis. Johansen test for determining cointegration showed that the GDP has significant positive long run relationship with FDI inflows. In contrast, there was an inverse relationship between EXP and FDI inflows. Results also show that FDI, EXP and the GDP series in Malaysia are I (1) series. In conclusion, the ability of a country in manipulating its' own resources is significant in generating the economic growth. It is recommended for future researchers to include other economic indicators such as interest rate, exchange rate and inflation rate in explaining additional factors contributing to FDI inflows.